1982
DOI: 10.1515/znc-1982-5-604
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Fluctuation of Quinolizidine Alkaloid Accumulation in Legume Plants and Photomixotrophic Cell Suspension Cultures

Abstract: Lupinus, Baptisia, Sarothamnus, Diumal Rhythm, Photomixotrophic Cell Suspension Cultures, Quinolizidine AlkaloidsFluctuations of quinolizidine alkaloid content in leaflets of Lupinus polyphyllus, L. hartwegii, Baptisia australis, and Sarothamnus scoparius were studied over a 36 h period. The alkaloid contents reached their maximum at noon or early afternoon, and their minimum during the night. The amplitudes of diumal variations in alkaloid levels lay within a range of 60 to 470% of the early morning contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…However, the activity of the enzymes of lupanine biosynthesis, lysine decarboxylase (3,141 and oxosparteine synthase [7,8], which are localized in the chloroplast [9], is similar to, or lower only by one order magnitude than, the respective enzyme activities in the plant [15]. We concluded that lupin alkaloids are actually formed by the cells, but are not accumulated to a marked degree, since they are rapidly degraded which is also an important feature of lupin plants and of other plant species [16,17]. Thus, the alkaloid turnover seemed to us an interesting possibility for the manipulation of alkaloid metabolism.…”
Section: Resultsmentioning
confidence: 68%
“…However, the activity of the enzymes of lupanine biosynthesis, lysine decarboxylase (3,141 and oxosparteine synthase [7,8], which are localized in the chloroplast [9], is similar to, or lower only by one order magnitude than, the respective enzyme activities in the plant [15]. We concluded that lupin alkaloids are actually formed by the cells, but are not accumulated to a marked degree, since they are rapidly degraded which is also an important feature of lupin plants and of other plant species [16,17]. Thus, the alkaloid turnover seemed to us an interesting possibility for the manipulation of alkaloid metabolism.…”
Section: Resultsmentioning
confidence: 68%
“…In addition to the biosynthesis of aromatic amino acids, the synthesis of terpenoids from mevalonic acid and part of the synthesis of conine have been shown to take place here. The role of chloroplasts is confirmed by the localization of enzymes involved in the synthesis oflupanine and sparteine in chloroplasts from Lupinus polyphyllus cell suspension cultures (Wink and Hartmann 1982). In Capsicum chromoplasts the stroma is the site of synthesis for the carotenoid phytoene.…”
Section: Synthesismentioning
confidence: 88%
“…QA were extracted and determ ined according to standard methods as outlined in previous papers [2,4,6,7],…”
Section: Alkaloid Extraction and Determinationmentioning
confidence: 99%
“…Decaying lupins, however, were readily consumed. All these experiments with intact plants had the dis advantage that the alkaloid content of lupins is variable within plants and within tim e [4] and that other mollusc repellent compounds m ight also be present which could obscure the influence of alkaloids. Therefore we have devised experim ents em ploy ing "artificial" diets, to which specified am ounts of QA were added, so QA content was the only variable of the system.…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation